Fall‐Related Hospitalizations in Nursing Home Residents Co‐Prescribed a Cholinesterase Inhibitor and Beta‐Blocker. Issue 11 (15th August 2020) - Watt, Jennifer A.; Campitelli, Michael A.; Maxwell, Colleen J.; Guan, Jun; Maclagan, Laura C.; Gomes, Tara; Bokhari, Mahmoud; Straus, Sharon E.; Bronskill, Susan E.
Abstract : BACKGROUND/OBJECTIVES: To examine the association between hospitalization for a fall‐related injury and the co‐prescription of a cholinesterase inhibitor (ChEI) among persons with dementia receiving a beta‐blocker, and whether this potential drug‐drug interaction is modified by frailty. DESIGN: Nested case‐control study using population‐based administrative databases. SETTING: All nursing homes in Ontario, Canada. PARTICIPANTS: Persons with dementia aged 66 and older who received at least one beta‐blocker between April 2013 and March 2018 following nursing home admission (n = 19, 060). MEASUREMENTS: Cases were persons with dementia with a hospitalization (emergency department visit or acute care admission) for a fall‐related injury with concurrent beta‐blocker use. Each case (n = 3, 038) was matched 1:1 to a control by age (±1 year), sex, cohort entry year, frailty, and history of fall‐related injuries. The association between fall‐related injury and exposure to a ChEI in the 90 days prior was examined using multivariable conditional logistic regression. Secondary exposures included ChEI type, daily dose, incident versus prevalent use, and use in the prior 30 days. Subgroup analyses considered frailty, age group, sex, and history of hospitalization for fall‐related injuries. RESULTS: Exposure to a ChEI in the prior 90 days occurred among 947 (31.2%) cases and 940 (30.9%) controls. In multivariable models, no association was found between hospitalization for a fall‐related injury and prior exposure to a ChEI in persons with dementia dispensed beta‐blockers (adjusted odds ratio = .96, 95% confidence interval = .85–1.08). Findings were consistent across secondary exposures and subgroup analyses. CONCLUSION: Among nursing home residents with dementia receiving beta‐blockers, co‐prescription of a ChEI was not associated with an increased risk of hospitalization for a fall‐related injury. However, we did not assess for its association with falls not leading to hospitalization. This finding could inform clinical guidelines and shared decision making between persons with dementia, caregivers, and clinicians concerning ChEI initiation and/or discontinuation.